Consumer Trust Formation and Behavioral Dynamics in Fintech Powered Digital Insurance Platforms - Celestin, Mbonigaba; Vasuki, M.; Dinesh Kumar, A.; Riyasdeen, S. (Madhesh Journal of Interdisciplinary Research, 2026)
We examine how fintech powered digital insurance platforms shape consumer trust formation across global markets and regulatory regimes. We use a structured platform level dataset covering 37 licensed digital insurance platforms drawn from a confirmed global population of 612 platforms, with observations spanning diverse institutional environments. We model trust as a behavioral outcome driven by platform security, service transparency, and user experience, while accounting for the conditioning role of regulatory credibility. We find that robust security features anchor trust intensity and reduce perceived risk, transparent service design stabilizes continued use and purchase commitment, and intuitive user experience reinforces behavioral continuity rather than initial belief formation. We further show that regulatory credibility strengthens and stabilizes these relationships by converting platform signals into durable consumer action. The core contribution lies in introducing a behavioral trust model that explains how trust emerges through observable actions rather than stated perceptions and why similar platforms perform differently across jurisdictions. The findings refine trust theory by positioning trust as staged and institutionally embedded, and they offer clear guidance for platform design and regulatory policy aimed at strengthening adoption, commitment, and resilience in digital insurance markets.